Re-envisioning the MLS : perspectives on the future of library and information science education - Percell, Johnna; Sarin, Lindsay C.; Jaeger, Paul T., 1974-; Bertot, John Carlo (Advances in librarianship, 2018)
At the heart of any discussion about the future of libraries is the future of librarians--and how well our instructional programs, especially the Master of Library Science (MLS) degree, prepare them for their careers. This book continues the critical conversations around preparing future librarians.